SOME INVESTIGATIONS ON NON-LINEAR WAVE PROPAGATION IN GASEOUS MEDIA - Nath, Triloki (iit bhu varanasi, 2017)
Fluid dynamics is the branch of applied science which is concerned with the movement of fluids. Mainly there are two types of fluid, incompressible and compressible fluids. Here our main attention is to study the problems of compressible fluid. The first International congress on gas dynamics was convened in Rome in 1935. The intensive development of gas dynamics began during and after the second world war in connection with the wide use of gas dynamics in technology: jet aviation, rocket weaponry, rocket and jet engines; supersonic aircraft and missiles etc. We are familiar with the propagation characteristics of light and sound waves. Violent disturbances such as, resulting from detonation of explosives, flow through rocket nozzles, supersonic flight of projectiles or from impact on solids differ from the linear phenomena of sound, light or electromagnetic signals. In contrast to the latter, their propagation is governed by non-linear partial differential equations, and as a consequence the familiar laws of superposition, reflection, and rarefaction ceases to be valid but even more novel features appear, among which the occurrence of shock fronts is the most significant. Across shock fronts the medium undergoes sudden change in velocity, pressure and temperature.
TtHIS THESIS SUBMITTED BYIIT BHU VARANASI pHD SCHOLAR AND SUPERVISED BY
Keywords: NON-LINEAR WAVE; GASEOUS MEDIA